Women of the Terreiro: the Tambor de Mina as a talisman of re-existence in the quilombola territory of Santa Rosa dos Pretos (Itapecuru-Mirim/MA, Brazil) (Simbiótica. Revista Eletrônica, 2025)
This text is a fragment of a doctoral research in Sociology and was only possible due to more than 10 years of writing with quilombola women who are on the front line in the defense of the Santa Rosa dos Pretos quilombola territory, Itapecuru-Mirim/MA, Brazil. This text aims to broaden the debate on the protagonism of quilombola women in their relationship with the quilombola territory and the terreiro. Based on this, Tambor de Mina is a religion of African origin, a safe space and an existential force that emanates from Mother Nature that women activate in the fight against predatory development. Based on the ontologies present in the relationships with the enchanted ones, quilombola women create and recreate possibilities of existence for themselves and their territory. Finally, we consider that this enchanted confluence allows the proposition of other narratives, to speak of us winning, as our master Nêgo Bispo taught us.
Keywords: Mina Drum. Black women. Enchanted. Resistance.